The Analysis Effectiveness of Guided Inquiry Implementation to Improve Students’ Science Process Skills - Kartika Sulistyani; Sifak Indana; Elok Sudibyo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
In improving science process skills, several learning approaches are carried out by teachers to achieve these objectives. One of the learning approaches used is the guided inquiry implementation. The objective of this research was to analyse effectiveness of the guided inquiry implementation to improve science process skills for elementary, junior high, and senior high school students. The research method used is study literature from various studies that have been published in journals, both nationally and internationally. Based on the analysis of 30 articles using the guided inquiry implementation, it is concluded that this learning approach is effective in improving science process skills, but teachers need to be aware for some strengths and weaknesses of this learning approach, so they need to be creative and innovative to develop the method used based on the characteristics of students in order to achieve the objective. Additionally, the use of the guided inquiry implementation can also improve long term memory, critical and creative thinking skills, motivation to learn science, and improve cognitive learning outcomes in science.